The Influence of Perceived Organizational Support and Self Efficacy on Employee Engagement in Generation Z DKI Jakarta - Ferawati, Neli (Growth: Journal Management and Business, 2023)
This research aims to analyze the influence of perceived organizational support and self-efficacy on employee engagement in generation Z in DKI Jakarta. The research was conducted using quantitative methods on 115 generation Z respondents who worked in DKI Jakarta, selected using a purposive sampling technique. Data was collected using a Likert scale questionnaire and analyzed using SmartPLS to test the influence of the independent variable on the dependent variable. The research results show that perceived organizational support and self-efficacy have a positive and significant effect on employee engagement. Self efficacy has a stronger influence than perceived organizational support. All independent variables were able to explain 65.3% of the variance in employee engagement. The research implication is that organizations need to increase perceived organizational support and self-efficacy in order to increase employee engagement for generation Z. Future research needs to consider additional variables that have the potential to influence employee engagement.